Theory of Mind in Pre-school Aged Children: Influence of Maternal Depression and Infants’ Self-Comforting Behavior - Nonnenmacher, Nora; Müller, Mitho; Taczkowski, Joana; Zietlow, Anna-Lena; Sodian, Beate; Reck, Corinna (Frontiers in Psychology, 2021)
A milestone of child development is Theory of Mind (ToM): the ability to attribute mental states, especially beliefs and desires, to other persons and to understand that their behavior is guided by mental states. The learning process about the mental world also takes place in social communication and interaction, beginning in infancy. Therefore, the quality of caregiver-child-interaction is assumed to play a crucial role in ToM-development. Infancy is assumed to be a sensitive period for the development of social skills through interaction. Due to limited self-regulatory skills, infants depend on sensitive behavior of their caregivers to regulate affective states and physiological arousal, and in turn, mutually regulated affects allow the infant to gradually acquire the capability to self-regulate negative affective states. Effective and adequate affect regulation is an important prerequisite for environmental interaction and thus for the development of socio-emotional skills. It is well known, that the ability to sensitively interact with the child is often impaired in mothers with affective disorders. The present study investigated the relation of dyadic interactional processes and self-regulatory abilities in infancy and later ToM in pre-school aged children of clinically depressed mothers and healthy controls. The sample comprised of N=55 mother-child dyads, n=22 diagnosed with postpartum or lifetime depression according to DSM-IV and n=33 healthy controls. Mother-infant-interaction was videotaped during the Face-to-Face-Still-Face paradigm. At 3 and 42 months postpartum mothers were interviewed with the SCID-I to evaluate maternal psychopathological status according to DSM-IV. At the age of M=4.0 years, children’s ToM abilities were assessed using content-false-belief and location-false-belief tasks. The results of this study show that contrary to our hypotheses, maternal depression did not impair the development of children’s ToM-abilities per se. Rather, an interaction effect highlights the role of infant’s self-comforting behavior during mother-infant interaction in infancy (three months postpartum) for ToM-development at pre-school age; this association was distinct for female in comparison to male children. The results of this longitudinal study shed light on the discussion, how maternal depression influences child development and point in the direction that self-comforting behaviors in infancy can also be seen as a resource.